STRATEGI PENGEMBANGAN PRODUK JAMU HERBAL UMKM MAKAARUIEN DI KOTA MANADO (Development Strategy of Makaaruien UMKM Herbal Jamu Products In Manado City) - Meidy Kevin Tandaju; Paulus A. Pangemanan; Melissa L. G. Tarore (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The objective of this research is to analyze the development strategies of herbal medicinal products at MSMEs (Micro, Small, Medium Enterprises) Makaaruien. This research was conducted from July to August 2020. The data used in this study are primary data. Primary data were obtained from direct interviews with respondents using questionnaires. Sampling method using purposive sampling method, as many as 4 samples based on the level of importance, knowledge, understanding experience. Samples taken are business owners, workers consumers. The analysis used in this study is the SWOT analysis (Strengths, Weakness, Opportunities, Threats) which is formulated in the Internal Factor Analysis Strategy (IFAS) Matrix and the External Factor Analysis Strategy (EFAS) Matrix. The results showed that the MSME strategy of Makaaruien was in quadrant I, which supported aggressive policies, namely the strategy to continue in developingÂ Â products with consistent processing without chemicals, because herbal medicines are always sought after by the wider community.Keywords: development strategy,SWOT analysis, herbal medicine, MSME.